Verbal Cuing Is Not the Path to Enlightenment. Psychological Effects of a 10-Session Hatha Yoga Practice - Csala, Barbara; Ferentzi, Eszter; Tihanyi, Benedek T.; Drew, Raechel; Köteles, Ferenc (Frontiers in Psychology, 2020)
Verbal instructions provided during yoga classes can differ substantially. Yoga instructors might choose to focus on the physical aspects of yoga (e.g., by emphasizing the characteristics of the poses) or they might take a more spiritual approach (e.g., by mentioning energy flow and chakras). The present study investigated the effects of verbal cues during yoga practice on various psychological measures. 84 female students (22.0±3.80 years) participated in the study. Two groups attended a beginner level hatha yoga course in which physically identical exercise was accompanied by different verbal cues. The so-called “Sport group” (N=27) received instructions referring primarily to the physical aspects of yoga practice, while the “Spiritual group” (N=23) was additionally provided with philosophical and spiritual information. A control group (N=34) did not receive any intervention. Mindfulness, body awareness, spirituality, and affect were assessed one week before and after the training. 2 x 3 mixed (time x intervention) ANOVAs did not show an interaction effect for any of the variables. However, when the two yoga groups were merged and compared to the control group, we found that spirituality increased, and negative affect decreased among yoga participants. In conclusion, yoga practice might influence psychological functioning through its physical components, independent of the style of verbal instructions provided.